2021
DOI: 10.1007/s10904-020-01842-w
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption Characteristics of WFD Heavy Metal Ions on New Biosourced Polyimide Films Determined by Electrochemical Impedance Spectroscopy

Abstract: In this work, innovative biosourced polyimide polymers were derived from novel combinations of monomers (Isosorbide, 6-FDA and amine cardo). These polymers were obtained with satisfactory yields by polycondensation of different percentages of isosorbide and of 6-FDA (from 100% to 0%). The synthesized polyimides had number average molecular weight in the 17600 -22000 g/mol range, and they were stable well above 451 °C (5% weight loss in N2). The glass transition temperature (Tg) were found to be in the range of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…In recent years, polymers derived from biomass have been extensively studied, and numerous investigations were conducted including the development of polymers containing heterocyclic moieties derived from biomass [16][17][18]. Recently, it has been shown that the development of heterocyclic bio-based polymers derived from Glux [19] and isosorbide [20,21] offers a good capacity to adsorb a wide variety of chemical compounds with diverse chemical structures.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, polymers derived from biomass have been extensively studied, and numerous investigations were conducted including the development of polymers containing heterocyclic moieties derived from biomass [16][17][18]. Recently, it has been shown that the development of heterocyclic bio-based polymers derived from Glux [19] and isosorbide [20,21] offers a good capacity to adsorb a wide variety of chemical compounds with diverse chemical structures.…”
Section: Introductionmentioning
confidence: 99%
“…Whatever the repetition unit in the isosorbide-based polymer, etherpyridine [15], phosphine [17], imide [18] or pyridine [19], the introduction of isosorbide improve the adsorption properties of polar pollutants and their metabolites compared to the bisphenol A-based polymers. The obtained results were explained by the attractive effect of the bio-based diols (isosorbide or glux) to generate hydrophilicity and wettability of the resulting linear polymer that subsequently regulate the availability of the adsorption sites and the dispersion of the polymer in water.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the challenge consists in the synthesis and characterization of a new partially biosourced synthon from the combination of isosorbide and pyridine that can participate in the design of six new co‐poly(ether‐pyridine)s in order to develop new adsorbent phases based on isosorbide with different structures. The integration of isosorbide into synthon can generate attractive hydrophilicity, wettability, superior rigidity, high‐thermal property and biodegradability, as well as nontoxicity 36 . Lately, homopolymers containing a pyridine structure substituted with a basic character motif have shown particular interest as potential adsorbents for micropollutants.…”
Section: Introductionmentioning
confidence: 99%